Analisis Perbandingan Kinerja Keuangan Sebelum Dan Sesudah Akuisisi Pada PT. Xl Axiata Tbk Tahun 2014 - Krisna Dwi Prasetyo; Indah Listyani; Edi Murdiyanto (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
A company needs to pay attention to financial performance so that it can see the extent of the company's position by analyzing financial reports. This research aims to determine the comparison of financial performance before and after the acquisition of PT. XL Axiata Tbk. in 2014 using the ratio Return On Assets, Return On Equity, Net Profit Margin.This type of research is descriptive with quantitative data taken secondary from the balance sheet and profit and loss report of PT. Pakuwon Jati Tbk for 2011-2017. Samples were taken from the population according to the saturated sampling method. The results of the research that has been carried out show that the financial performance of ROA, ROE AND NPM is almost the same because the average before the acquisition decreased while after the acquisition it increased which can be said to be good after the acquisition.